Base Composition Characteristics of Mammalian miRNAs - Wang, Bin (Journal of Nucleic Acids, 2013)
MicroRNAs (miRNAs) are short RNA sequences that repress protein synthesis by either inhibiting the translation of messenger RNA (mRNA) or increasing mRNA degradation. Endogenous miRNAs have been found in various organisms, including animals, plants, and viruses. Mammalian miRNAs are evolutionarily conserved, are scattered throughout chromosomes, and play an important role in the immune response and the onset of cancer. For this study, the author explored the base composition characteristics of miRNA genes from the six mammalian species that contain the largest number of known miRNAs. It was found that mammalian miRNAs are evolutionarily conserved and GU-rich. Interestingly, in the miRNA sequences investigated, A residues are clearly the most frequent occupants of positions 2 and 3 of the 5′ end of miRNAs. Unlike G and U residues that may pair with C/U and A/G, respectively, A residues can only pair with U residues of target mRNAs, which may augment the recognition specificity of the 5′ seed region.